The epileptogenic zone in children with tuberous sclerosis complex is characterized by prominent features of focal cortical dysplasia - Hulshof, Hanna M; Benova, Barbora; Krsek, Pavel; Kyncl, Martin; Lequin, Maarten H; Belohlavkova, Anezka; Jezdik, Petr; Braun, Kees P J; Jansen, Floor E (Epilepsia open, 2021)
OBJECTIVE: Patients with tuberous sclerosis complex (TSC) present with drug-resistant epilepsy in about 60% of cases, and evaluation for epilepsy surgery may be warranted. Correct delineation of the epileptogenic zone (EZ) among multiple dysplastic lesions on MRI represents a challenging step in pre-surgical evaluation. METHODS: Two experienced neuroradiologists evaluated pre- and post-surgical MRIs of 28 epilepsy surgery patients with TSC, assessing characteristics of tubers, cysts, calcifications, and focal cortical dysplasia (FCD)-resembling lesions. Utilizing multiple metrics, we compared MRI features of the EZ-defined as the resected area in TSC patients who achieved seizure-freedom 2 years after epilepsy surgery-with features of other brain areas. Using combinatorial analysis, we identified combinations of dysplastic features that are most frequently observed in the epileptogenic zone in TSC patients. RESULTS: All TSC-associated dysplastic features were more frequently observed in the EZ than in other brain areas (increased cortical thickness, gray-white matter blurring, transmantle sign, calcifications, and tubers; Kendal's tau 0.35, 0.25, 0.27, 0.26, and 0.23, respectively; P value <.001 in all). No single feature could reliably and independently indicate the EZ in all patients. Conversely, the EZ was indicated by the presence of the combination of three of the following features: tubers, transmantle sign, increased cortical thickness, calcifications, and the largest FCD-affected area. Out of these, the largest FCD-affected area emerged as the most reliable indicator of the EZ, combined either with calcifications or tubers. SIGNIFICANCE: The epileptogenic zone in TSC patients harbors multiple dysplastic features, consistent with focal cortical dysplasia. A specific combination of these features can indicate the EZ and aid in pre-surgical MRI evaluation in epilepsy surgery candidates with TSC.
Keywords: Tuberous Sclerosis; Epilepsy; epilepsie; pre-surgical evaluation; tuberous sclerosis complex; mozek; magnetic resonance imaging; dítě; Malformations of Cortical Development; Child; magnetická rezonanční tomografie; Magnetic Resonance Imaging; Brain; Humans; malformace mozkové kůry; epilepsy surgery; focal cortical dysplasia; tuberózní skleróza; lidé